Fragile and Conflict-Affected Food Systems Area of Work Newsletter: June 2025 - Carrillo, Lucia; Hollerich, Gillian; Kosec, Katrina (CGIAR System Organization, 2025)
We are pleased to announce that the CGIAR Research Initiative on Fragility, Conflict, and Migration will be continuing its work as the Fragile and Conflict-Affected Food Systems (FCA) Area of Work under the CGIAR Food Frontiers and Security Science Program. As a part of our new portfolio of work, we are launching a Fragility to Stability Policy Seminar Series!